2022
DOI: 10.3390/separations9100283
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Eriochrome Black T Dye Using Activated Carbon of Waste Hemp (Cannabis sativa L.) Grown in Northern Morocco Enhanced by New Mathematical Models

Abstract: In the present work, the adsorption behavior of Eriochrome Black T (EBT) on waste hemp activated carbon (WHAC) was examined. The surface of the WHAC was modified by H3PO4 acid treatment. The surface and structural characterization of the adsorbents was carried out using Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) analysis. The effect of influential adsorption parameters (pH, contact time, dosage, and initial concentration) on the adsorption of EBT onto WHAC was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In this regard, sustainable sorbents that are based on hemp fibres have been studied with high dye sorption features [107], [108]. The commonly studied dye for sorption properties of hemp fibres is methylene blue dye [109]. Viscusi et al [110] reported hemp fibres for methylene blue dye adsorption from aqueous media.…”
Section: Water Remediationmentioning
confidence: 99%
“…In this regard, sustainable sorbents that are based on hemp fibres have been studied with high dye sorption features [107], [108]. The commonly studied dye for sorption properties of hemp fibres is methylene blue dye [109]. Viscusi et al [110] reported hemp fibres for methylene blue dye adsorption from aqueous media.…”
Section: Water Remediationmentioning
confidence: 99%
“…Another effective method for the removal of dye, due to its low cost and easy installation, is adsorption [15]. El Mansouri et al [16] removed up to 62% of Eriochrome Black T (EBT) using H 3 PO 4 -modified activated carbon (derived from Cannabis sativa L.) at a pH of 7, a contact time of 3 h, and an initial concentration of dye at 10 mg•L −1 . Moreover, in this study, the maximum adsorption capacity was 14.02 (mg•g −1 ) in terms of the Langmuir isotherm study.…”
Section: Summary Of Published Articlesmentioning
confidence: 99%